ANTIPROLIFERATIVE, ADME AND POTENTIAL IN SILICO G6PDH INHIBITORY ACTIVITY OF NOVEL 2-(1-BENZOFURAN-2-YL)-4-(5-PHENYL-4H-1, 2, 4-TRIAZOL-3-YL) QUINOLINE DERIVATIVES - S., Santoshkumar; K., Manjulatha; D., Satyanarayan N.; R., Anantacharya; S., Harishkumar; N., Harishkumar H.; S., Yallappa; L., Dhananjaya B. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objectives: Synthesis of new 2-(1-benzofuran-2-yl)-4-(5-phenyl-4H-1, 2, 4-triazol-3-yl) quinoline and its derivatives for antiproliferative potential against cancer cells. Methods: The general methods were employed for the synthesis and the structures were confirmed by IR, 1H-NMR, 13C-NMR and mass spectral analysis. The antiproliferative activity was performed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and molecular docking study were performed by Auto Dock Tools. In silico Absorption-Distribution-Metabolism-Excretion-Toxicity (ADMET) study for the drug, likeliness was carried out on ACD/lab-2. Results: The compound 3l showed 44, 44, 38 and 37 % inhibition against MCF-7, HepG2, Colo205 and HeLa cell lines, respectively; whereas, the compounds 3i and 3j exhibited 49 and 42 % inhibition against MCF-7 cell line. The molecular docking study revealed that the compound 3i has the lowest binding energy (-8.60 Kcal mol-1), suggesting to be potentially best inhibitor of Glucose-6-phosphate dehydrogenase (G6PDH). The in silico ADME analysis also revealed that compound 3i does not violate any of the Lipinski rules of five and has the best stimulative human colonic absorption up to 95 %. Conclusion: The study reveals that the compounds containing benzofuran coupled nitrogen heterocycles are essential for activity as they possess excellent drug-like characteristics.Â 